Implementasi Sistem Monitoring dan Manajemen Timbangan Muatan Kendaraan Berbasis Android: (Studi Kasus: Jembatan Timbang) - Nabila Shalasyifa; Fatoni Fatoni (Pusat Riset dan Inovasi Nasional, 2026)
The digital era demands weighbridge services to be faster and more efficient. CV. Akbar Multiscale already has a web-based scale management system, however driver registration is still carried out manually and reporting is difficult to access directly, causing delays and recording errors. This research aims to implement an Android-based vehicle load weighbridge monitoring and management system that can be accessed through mobile devices. The system was developed using the Agile Development method which enables the development process to be carried out gradually, flexibly, and adapting to user needs in the field. System implementation utilizes Progressive Web Application (PWA) technology that can be accessed through Android devices without additional application installation. The system is equipped with digital driver registration features, role-based user authentication, IoT scale simulation integration for automatic weight data input, and real-time reporting modules that are easily accessible anytime through mobile devices. Black Box Testing results show that all main system features function properly with a high success rate. Trials at the CV. Akbar Multiscale weighbridge showed positive responses from users regarding the ease of access to the Android-based system and the efficiency of the weighing process.